Adesão bacteriana e formação de biofilme em superfícies de titânio com diferentes topografias - Agnol, Claudio Zeferino Dal (2013)
Risk factors associated with peri-implantitis are related to the composition of the biofilm around the implant and the ability of bacteria to adhere to the surface. The aim of this study was to evaluate the biofilm formation on the different surfaces of commercially pure titanium (CP Ti) grade 4 in the times of 12, 24, 48 and 168 hours by the microcosm technique and scanning electron microscopy (SEM) . Biofilms were formed in microwell plates over cp Ti (N = 160) discs, having the saliva as inoculum (microcosms) from a donor over 10 discs for each inoculum (n = 10). There were 40 specimens for each type of surface, namely: plain (control - L), blasted with aluminum oxide (Al2O3 - J), subtraction by nitric acid attack (A), and finally blasted with Al2O3 added by nitric acid attack (JA). A disc of each condition (4) was evaluated previously to inoculation as to its topography by SEM and average roughness (Ra), and 16 were evaluated by SEM after the microcosm technique, totaling 20 specimens. Data gathered were analyzed by the two-factor ANOVA variance test and Tukey for comparison of means (p <0.05). There was statistical difference between the control surface (25,34) and A (19,15) regarding J and JA (43.83 and 32.06) in the CFU/ mg counts in the first 12 hours, when biofilm formation was higher in J (Ra = 0.62 μm) and JA (Ra = 0.51 μm). It was observed that all surfaces made possible microbial growth, regardless of treatment received